2020
DOI: 10.3389/fmicb.2020.02036
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a Manuka Honey Wound Gel Is Associated With Changes in Bacterial Virulence and Antimicrobial Susceptibility

Abstract: The use of manuka honey for the topical treatment of wounds has increased worldwide owing to its broad spectrum of activity towards bacteria in both planktonic and biofilm growth modes. Despite this, the potential consequences of bacterial exposure to manuka honey, as may occur during the treatment of chronic wounds, are not fully understood. Here, we describe changes in antimicrobial susceptibility and virulence in a panel of bacteria, including wound isolates, following repeated exposure (ten passages) to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…This study recognized that honey possesses antibacterial properties upon resistant bacteria, and can also promote effective wound healing [93]. Following this study, a significant amount of work using manuka honey confirmed its effects against MRSA in vitro [24,[94][95][96][97][98][99][100] and in vivo [101], vancomycin-resistant S. aureus [91], and vancomycin-resistant enterococci (VRE) [100]. MRSA and VRE are considered the foremost pathogens that often infect chronic wounds in the earlier stages [96].…”
Section: Honey Against Antibiotic-resistant Bacteriamentioning
confidence: 95%
See 1 more Smart Citation
“…This study recognized that honey possesses antibacterial properties upon resistant bacteria, and can also promote effective wound healing [93]. Following this study, a significant amount of work using manuka honey confirmed its effects against MRSA in vitro [24,[94][95][96][97][98][99][100] and in vivo [101], vancomycin-resistant S. aureus [91], and vancomycin-resistant enterococci (VRE) [100]. MRSA and VRE are considered the foremost pathogens that often infect chronic wounds in the earlier stages [96].…”
Section: Honey Against Antibiotic-resistant Bacteriamentioning
confidence: 95%
“…More recently, Mokhtar et al evidenced that long-term exposure of different strains of S. aureus, S. pyogenes, P. aeruginosa, E. coli, MRSA and S. epidermidis to manuka honey was not able to generate isolates with a reduced susceptibility to honey following a similar time frame in which resistance to macrolides was generated [97]. Moreover, it was suggested that the iron chelation capacity of manuka honey affects multiple diverse physiological processes in bacteria and would contribute to the lack of bacterial resistance to honey [75].…”
Section: What About Honey-resistance Acquisition?mentioning
confidence: 99%
“…This was the result of observed antimicrobial properties of methylglyoxal, which can promote wound healing and exhibit potent activity against various planktonic and biofilm-forming Gram-positive and Gram-negative pathogenic bacteria, including wound pathogens [19]. Interestingly and importantly, increased in vitro sensitivity was observed in bacterial strains treated with Manuka honey to clinically used antibiotics, compared with untreated bacteria [20].…”
Section: Review Honey As a Wound Remedymentioning
confidence: 99%
“…However, resistance to silver was observed in certain wound-infecting bacteria, such as E. coli and Acinetobacter baumannii [17]. Manuka honey, as a natural alternative, was successful in preventing biofilm formation by P. aeruginosa and S. aureus and limited the possibility of developing resistance, making its potential therapeutic use in treating wound infections very promising [18][19][20].…”
Section: Wound Infectionsmentioning
confidence: 99%
“…The antibiofilm activity of peptides was evaluated by the minimum biofilm inhibitory concentration (MBIC) and the minimum biofilm eradication concentration (MBEC) assays against S. aureus and P. aeruginosa as previously described [26,27] with some modifications. For the MBIC assay, 1 × 10 6 cfu/ml bacterial culture in Muellar-Hinton Broth (MHB) was mixed with antimicrobial peptides (1-512 mg/l) in a 96-well plate, followed by incubation for 24 h at 37C at 120 rpm.…”
Section: Antibiofilm Assaymentioning
confidence: 99%